Mutagenicity induced by the hydroalcoholic extract of the medicinal plant Plathymenia reticulata Benth - Della Torre, A.; Albuquerque, L. B. L.; Farrapo, N. M.; Oshima-Franco, Y.; Santos, M. G.; Tavares, R. V. S.; Rodas, A. C. D.; Dal Belo, C. A.; Cardoso, C. R. P. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Groppo, F. C.; Lopes, P. S. (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Plathymenia reticulata Benth has an anti-inflammatory effect and is capable of neutralizing the neuromuscular blockade induced by Bothrops jararacussu or Crotalus durissus terrificus venoms, probably by precipitating venom proteins (an effect caused by plant tannins). The present study aimed to evaluate the mutagenic activity of P. reticulata by using the Salmonella mutagenicity assay (Ames test) and the micronucleus test in CHO-K1 cells. P. reticulata extract concentrations of 2.84, 5.68, 11.37, and 19.90 mg/plate were assayed by the Ames test using TA97a, TA98, TA100 and TA102 bacterial strains, with (+S9) and without (-S9) metabolic activation. Concentrations of 5, 1.6 and 0.5 mu g/mL of P. reticulata extract were used for the micronucleus test. P. reticulata extract was mutagenic to TA98 (-S9) and showed signs of mutagenic activity in TA97a and TA102 (both -S9) strains. Micronucleus test CBPI values showed that the endogenous metabolic system increased the number of viable cells when compared to the non-activated samples and the micronucleus frequency increased when the cells were treated in the absence of S9. We concluded that P. reticulata extract may present direct mutagenic properties.
Keywords: Ames test; micronucleus test; mutagenicity; plant extract; Plathymenia reticulata